Religious Character Formation Through Islamic Habituation in Primary Education - Nurizah, Ainawa Kholilatul; Amrullah, Muhlasin (Indonesian Journal of Islamic Studies, 2024)
The general background character education plays a crucial role in shaping moral and ethical behavior in students, particularly within primary education settings. In Islamic educational institutions, there is a notable emphasis on integrating religious values into character development, with a focus on habituation practices to reinforce these values among students. However, there is limited empirical research that specifically examines the effectiveness of Islamic habituation as a method for strengthening religious character in primary education. This study aims to explore the implementation and impact of Islamic habituation on religious character formation among students at Muhammadiyah 1 Sidoarjo Elementary School. Findings reveal that the systematic application of Islamic habituation, including practices such as daily prayers, gratitude, and the 5S culture, significantly enhances students' moral behavior and engagement in religious activities. This research contributes to the existing body of knowledge by providing evidence of the positive outcomes of religious habituation in an educational context, emphasizing its role in character education. The results suggest that integrating Islamic habituation into primary education not only fosters individual moral development but also promotes a supportive community environment conducive to religious learning, thereby reinforcing the importance of character education within the broader educational framework. Highlights: Systematic Islamic habituation practices enhance students' moral behavior. Integration of religious values fosters a supportive community environment. Empirical evidence contributes to the understanding of character education in Islamic contexts. Keywords: Islamic Education, Character Formation, Habituation, Primary Education, Moral Development